Single-particle strength in neutron-rich 71Cu from the (d, 3He) proton pick-up reaction. (9th February 2015) - Franchoo, S; Morfouace, P; Assié, M; Azaiez, F; Beaumel, D; Boissinot, S; Borcea, R; Burgunder, G; Cáceres, L; Séréville, N De; Dombradi, Z; Elseviers, J; et al.
Abstract: We have measured the 72 Zn(d, 3 He) 71 Cu proton pick-up reaction in inverse kinematics at 38 MeV/u. A dedicated set-up was developed to overcome the experimental challenges posed by the low cross section of the reaction and the low energy of the outgoing 3 He particles. The excitation-energy spectrum was reconstructed and spectroscopic factors were obtained after analysis of the angular distributions in the finite-range Distorted-Wave Born Approximation (DWBA). The results show that unlike for the πf 5/2 orbital, the πf 7/2 singleparticle strength is not appreciably affected by the addition of neutrons beyond N = 40.